Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Materi Komponen Ekosistem Kelas V - Kharimah, Masitoh Nur; Widiyanto, Joko; Iswanto, Iswanto (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this learning is to see an increase in the learning outcomes of class V students at SDN Kandangan 1 Ngawi in science and technology subjects, Ecosystem component material using the Problem Based Learning (PBL) learning model. The subjects in this research were class V students at SDN Kandangan 1 Ngawi Regency with a total of 17 children. Data collection techniques in this research were observation, tests and documentation. The research data analysis technique uses quantitative and qualitative descriptive analysis. The results of this research show a significant improvement from each cycle. In the pre-cycle or before using the Problem Based Learning (PBL) learning model, it was discovered that only 23.52% of students or the equivalent of 4 children had achieved the science and science learning objectives on land ecosystem food chains. Furthermore, in cycle 1 there was a significant increase in learning outcomes as evidenced by the fact that 64.7% of students or the equivalent of 11 children had achieved the learning objectives. Continuing in the second cycle, learning outcomes also increased in the second cycle, amounting to 88.23% or the equivalent of 15 students having achieved this learning objective. The conclusion of this research is that there is an increase in student learning outcomes in science and science lessons on Ecosystem Components using the Problem Based Learning (PBL) learning model.